A New Experimental Approach Using Image Processing-Based Tracking for an Efficient Fault Diagnosis in Pantograph-Catenary Systems - Karakose, Ebru; Gencoglu, Muhsin Tunay; Karakose, Mehmet; Aydin, Ilhan; Akin, Erhan (Ieee-Inst Electrical Electronics Engineers Inc, 2017)
The periodical maintenance of railway systems is very important in terms of maintaining safe and comfortable transportation. In particular, the monitoring and diagnosis of faults in the pantograph catenary system are required to provide a transmission from the catenary line to the electric energy locomotive. Surface wear that is caused by the interaction between the pantograph and catenary and nonuniform distribution on the surface of a pantograph of the contact points can cause serious accidents. In this paper, a novel approach is proposed for image processing-based monitoring and fault diagnosis in terms of the interaction and contact points between the pantograph and catenary in a moving train. For this purpose, the proposed method consists of two stages. In the first stage, the pantograph catenary interaction has been modeled; the simulation results were given a failure analysis with a variety of scenarios. In the second stage, the contact points between the pantograph and catenary were detected and implemented in real time with image processing algorithms using actual video images. The pantograph surface for a fault analysis was divided into three regions: safe, dangerous, and fault. The fault analysis of the system was presented using the number of contact points in each region. The experimental results demonstrate the effectiveness, applicability, and performance of the proposed approach.
Keywords: Condition monitoring; fault diagnosis; image processing; pantograph-catenary system